Isolation and characterization of toxins from Xenorhabdus nematophilus against Ferrisia virgata (Ckll.) on tuberose, Polianthes tuberosa. (May 2018) - Hemalatha, Dhamodharan; Prabhu, Somasundaram; Rani, William Baby; Anandham, Rangasamy
Abstract: This study was aimed to evaluate the toxins of Xenorhabdus nematophilus bacterial isolate MDUStBa15 isolated from the nematode Steinernema carpocapsae that can parasitize two tailed mealybug Ferrisia virgata which is a new pest on tuberose. Soluble protein and organic fractions were characterized from cell free extract of X . nematophilus . Using SDS PAGE, presence of low molecular weight toxic proteins (12, 42 and 60 kDa) was observed in cell free extracts of X . nematophilus . Among these three proteins, 12 kDa was newly found in this study which showed anti-feedant activity and the maximum of 87.50% and 82.50% mortality of crawlers and adults of F. virgata, respectively at 72 h after treatment. GC-MS analysis of culture filtrates revealed the presence of five major compounds, all are exhibiting insecticidal property. Among several organic fractions, 1, 4 - epoxynaphthalene - 1 (2H) - methanol, 4, 5, 7-tris (1, 1 - dimethylethyl) - 3, 4 - dihydro; Pentacosane and Hexacosane were found in this study. Pot culture study revealed that an optimum dose of 5 ml/l of crude toxin caused the maximum mortality in crawlers (100%) and in adults (96.8%) of F . virgata at 72 h after spraying. In a field study application of 5 ml/l crude toxin along with biocontrol agent (Ladybird beetle - Cryptolaemus montrouzieri ) registered the 90.55% mortality in crawlers and 73.60% mortality in adults of F . virgata at 7 days after spraying. The present study provides the clear evidence for the toxicity of protein; organic fraction and crude toxin which was obtained from X . nematophilus isolate MDUStBa15 against F . virgata on tuberose both in lab and field conditions. Hence, it can be utilised to manage the F . virgata on tuberose. Highlights: Low molecular weight protein and organic fraction were characterized from cell free extract of X. nematophilus MDUStBa15. Toxic protein 12 kDa is found in this study which showed antifeedant and insecticidal activity against mealybug Ferrisia virgata. GC-MS analysis of culture filtrates revealed five major compounds, having insecticidal property, among them three were new. Toxicity of protein and culture filtrates against F. virgata on tuberose in in vitro and field conditions were evidenced.